THE EFFECTIVENESS OF USING EXCAVATOR IN THE CONSTRUCTION PROJECT OF PT. AGRO PLANKAN LESTARI PALM OIL FACTORY, SEKADAU REGENCY - Suhendra, Danu; Lusiana, Lusiana; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2024)
A construction project is a series of interrelated activities to achieve specific goals (buildings/construction) within a particular time, cost, and quality constraints. One crucial resource in this context is construction equipment or heavy machinery. West Kalimantan is renowned for its abundant palm oil production, including in Sekadau Regency. Due to the lack of palm oil processing factories, PT. Agro Plankan Lestari constructed a palm oil factory. The research findings indicate that the average performance efficiency of the excavator was 64% (considered good) for both excavators. However, the average Overall Equipment Effectiveness values for both operators were below the tolerance level set by the Japan Institute of Plant Maintenance (JIPM), which is 40%. The average overall equipment effectiveness values of excavator A obtained an average value of 39.82%, and excavator B obtained 41.69%.